Understanding Repeat Purchase Intention in Emerging E-Commerce Markets: A Systematic Review of Trust, Satisfaction, and Cultural Contexts - Susanti, Febsri; Wardi , Yunia; Abror, Abror; Dwita, Vidyarini; Evanita , Susi (Jurnal Sains Sosio Humaniora, 2026)
This systematic review aims to confirm trust, satisfaction and cultural contexts form the primary foundation for repeat purchase intentions in the current e-commerce market growing. Adopting the PRISMA guidelines, this study searched the ScienceDirect database using the string (repurchase intention AND local culture). From an initial pool of 1,873 publications, the systematic application of five inclusion criteria (2021–2025 timeframe, article type, subject area, and access type) narrowed the selection down to 24 final articles. The finding highlights that trust play role as main factor to reduces perception risk at a time increase belief consumer to the platform. While satisfaction ensure experience positive that encourages loyalty. On the other hand, the context culture strengthens relevance authenticity and experience effective, so that consumer feel more connected with product and services offered. The interaction of these three factors demonstrates how repurchase behavior is driven by engaging consumer experiences. The primary contribution of this research is the development of a novel conceptual framework integrating cultural dimensions into e-commerce behavior. Consequently, this study provides a comprehensive overview showing that repurchase intentions depend not only on technical service aspects but also heavily on the experiential and cultural dimensions that shape consumer decision-making.